O estreitar de laços musicais através da Física - Oliveira, Leonardo Silva de (Universidade Federal de São Carlos, 2023)
Motivated by the lack of musical activities in classroom and by the lack of interest in teaching physics mechanically static, aims to stimulate the musical sensitivity in side school outlook, using physical explanations to specify the wavy phenomenon in berimbau. Not only it is possible to get an opposite reaction, that the study will stimulate physics through the music. Upon a series of classes that theorized the concept of waves, sound waves, wavy phenomenon, wriggling strings, audio pipes, it becomes possible to detail the acoustic principle of a berimbau, that has a simple way to work: its acoustic box (calabash) vibrates in resonance with the string. The modes of vibration in musical instruments can be known and recognized using basic math formulas in taking into account the Berimbau dimensions. It is expected to the children to be active subjects able to measure, calculate, discuss and infer the harmonics present in the instrument. We seek to make clear the sound perception and appreciation linked to wave length in the instrument, to capture an afterthought physical-musical of the learner in order to stimulate a sensibility capable to note a simple and inseparable mathematical nature of the instrument. The target audience of these issue is high school students, specifically, the second year of high school.
Strengthening musical links through Physics
Keywords: Física; Educação musical; Berimbau; Ondas Sonoras; Physics; Musical education; Sound waves; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA GERAL